International law and the Arab-Israeli conflict - Sabel, Robbie (Cambridge : Cambridge University Press, 2022)
Drawing upon Robbie Sabel's first-hand involvement with many legal negotiations in the Arab-Israeli conflict, International Law and the Arab-Israeli Conflict examines international law in relation to the conflict by analysing its major events and agreements, both historical and contemporary. Outlining the role of international law from the collapse of the Ottoman Empire until the present day, it considers the legal elements of the various peace treaties that Israel has signed with its neighbouring Arab States. Using his expertise as a professor, practitioner and ambassador, Sabel endeavours to represent both sides of the conflict, offering a wealth of counter-arguments and adding his own legal interpretations. With this valuable resource, students and researchers working within a range of disciplines can fully appreciate the role of international law in the Arab-Israeli conflict.
Is international law relevant? -- The First World War -- The Zionist Movement and the 1917 Balfour Declaration -- Post World War I and the 1922 League of Nations Mandate for Palestine, 1920-1947 -- The 1947 Partition Plan -- Israel's Declaration of Independence -- The 1948 Arab-Israeli War -- 1949 Armistice Agreements -- The Arab refugee problem -- The 1967 Six Day War -- UN Security Council Resolution 242 -- Camp David 1978 -- 1979 Egypt-Israel Peace Treaty -- Taba Arbitration -- The legality of Israel exploitation of oil from Sinai -- The Oslo accords -- Israel-Jordan -- Post Oslo developments -- The status of the "West Bank" (Judea and Samaria) and the Gaza Strip -- Israel settlements in the West Bank -- Controversial elements of military administration -- Freedom of navigation through international waterways in the region -- Israel-Syria -- Jerusalem -- Controversial laws of war issues -- Is Palestine a state -- Water resources-Israel and neighbours -- Implications for future negotiations.
Title from publisher's bibliographic system (viewed on 07 Apr 2022).
Keywords: Arab-Israeli conflict -- Law and legislation; Israel -- International status; Palestine -- International status